Rotating Scan Strategy Induced Anisotropic Microstructural and Mechanical Behavior of Selective Laser Melted Materials and Their Reduction by Heat Treatments. Issue 12 (1st August 2021) - Diepold, Benedikt; Palm, Mathias Sebastian; Wimmer, Andreas; Sebald, Torsten; Höppel, Heinz Werner; Neumeier, Steffen; Göken, Mathias
Abstract : Choosing a properly optimized rotating scan strategy during the selective laser melting (SLM) process is essential to reduce residual stresses and thus to obtain homogeneous properties. Surprisingly, anisotropic material properties are found in several materials that are built with the often applied rotating stripes scan strategy of Electro‐Optical Systems (EOS) because the scan strategy avoids possible interactions of the laser beam with process by‐products and therefore excludes a range of scanning directions. Herein, the alloys Hastelloy X, Inconel 718, and stainless steel 316L are investigated. Vertically built specimens with a cylindrical gauge geometry show an oval deformation during tensile testing, indicating a mechanical anisotropy in the horizontal x ‐ and y ‐direction. Tensile tests along the x ‐ and y ‐direction reveal a deviation of the yield strength of 7% for Hastelloy X. Analyses of the microstructures show differences in the grain morphology, size, and texture in all three coordinate planes of the three materials. This anisotropic behavior can be explained by a detailed study of the texture and the calculated Schmid factors. Heat treatments can reduce the textural and mechanical anisotropy due to recrystallization of grains but requires annealing at sufficiently high temperatures and long times. Abstract : Three alloys are produced by selective laser melting using a rotating scan strategy that leaves out angles that are prone to cause an attenuation. This leads to oval cross sections of tensile specimens. Textures and calculated Schmid factors are used to explain anisotropic tensile properties and inhomogeneous deformation. Furthermore, it is investigated how heat treatments reduce the anisotropy.